INVESTIGATION OF PASSIVATION OF SURFACE STATES OF SINGLE CRYSTALLINE SILICON IN HETEROSTRUCTURES WITH AN INTEGRATED THIN AMORPHOUS LAYER - Chuchvaga N.А.; А.V. А.V.; Titov А.S.; Tokmoldin, N.S.; Tokmoldin, S.Zh.; Terukov Е.I. (Academic Scientific Journal of Computer Science, 2020)
This work presented in this publication is a continuation of works [1] and [2]. We have shown that in solar cells of the HIT structure, when the thickness of the embedded amorphous layer increases, the efficiency of the solar cell increases, but to a certain point of maximum. The increase in characteristics is due to an increase in the lifetime of non-basic charge carriers in a crystalline silicon substrate. This behaviour of the system can be explained by better passivation of surface States on the silicon substrate. The decrease in the efficiency of the solar cell after reaching the maximum is due to the increase of the resistance structure, which with a point contributes more to the characteristics of the solar cell than the contribution from the passivation of surface states. Using the PECVD method, amorphous silicon films with a thickness of 7, 30 and 50 nm were grown on a single-crystal commercial silicon substrate on both sides. Then, the lifetime of non-basic charge carriers was measured using the contactless Sinton method on these structures. Further, the samples were examined by photoluminescence at room temperature. Using this method, it was possible to obtain the dependence of the concentration of non-equilibrium charge carriers on the intensity of photoluminescence radiation. These dependences showed that the intensity is lower on samples with a lower thickness of amorphous silicon than in samples with a higher thickness of the amorphous layer. The detailed results of this work were first presented by the corresponding author in his dissertation [3], the theses of the work were presented at the conference of young scientists of KazNU [4] and only now the results are published as a full-fledged article in the journal.